The Poverty Focus of Country Programs : Lessons from World Bank Experience - Independent Evaluation Group (World Bank, Washington, DC, 2015)
The World Bank Group in 2013 made the elimination of extreme poverty by 2030 a central institutional focus and purpose. This evaluation examines how, and how well, the Bank Group has focused its support on poverty reduction over the past decade, and what lessons to draw from this moving forward. The lessons aim to strengthen the Bank’s country diagnostics, improve the design of country strategies, and build greater learning opportunities from program experience. Using country case studies, surveys, focus group meetings, systematic reviews of Bank products, and other instruments, the evaluation examines the consistency of poverty focus in each of four links in a causal chain: data, diagnostics, strategy formulation, and strategy implementation through lending and nonlending instruments. It reviews the adequacy of the information base and usefulness of the analytical underpinnings that support country strategy formulation and implementation. It also evaluates the consistency of the poverty focus throughout the evaluation chain and the strength and weakness of feedback loops.